Edukasi Kesehatan Reproduksi Remaja dan Penggunaan Bahan Alam dalam Melindungi Kesehatan Reproduksi pada Siswa SMAN 1 Pekanbaru - Saddam Muhdi; May Valzon; Huda Marlina Wati; Larysa Fernenda; Muhammad Al Fatih; Muhammad Nur Faisal Rizky; Reza Rizky Notisa; Rizka Prasetya Putri Dewi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Adolescent reproductive health knowledge remains suboptimal due to insufficient access to accurate, evidence-based educational resources. This challenge is further compounded by the dissemination of unreliable information, resulting in misconceptions and improper health practices. This study presents a community-based initiative aimed at enhancing reproductive health literacy among students of SMAN 1 Pekanbaru, with a particular focus on integrating the use of natural resources as a preventive strategy. The program addresses gaps in structured reproductive health education and leverages locally available natural resources to foster sustainable health practices. The initiative encompasses structured activities, including socialization sessions for students and educators, comprehensive training on reproductive health and the utilization of natural resources, and the deployment of technology to facilitate information dissemination. Implemented by a multidisciplinary team from the Faculty of Medicine, Universitas Abdurrab, the program is supported by ongoing mentorship and systematic evaluations using surveys and interviews. This initiative underscores the potential for sustained impact through partnerships with schools, local health agencies, and community organizations. By enhancing awareness and encouraging the adoption of natural, sustainable practices, the program serves as a translational application of research findings, with the potential for scalability to other educational institutions and broader community settings.